EVALUASI TINGKAT PARTISIPASI MASYARAKAT DALAM PENGELOLAAN IRIGASI DAERAH RAWA ANJIR SERAPAT KABUPATEN KAPUAS - Pining Sitohang (Lambung Mangkurat University Press, 2018)
Anjir Serapat I swamp area is about 160 km straight towards the boundary of South Kalimantan Province via the trans Kalimantan road with a functional area of ​​DIR Anjir Serapat Kapuas Regency of 3,248 Ha and it has great potential to increase agricultural production. The potential is still not optimal. This can be seen from the results of rice production that is still not optimal. To overcome these problems requires an approach to the community about the importance of managing the micro water system which is the responsibility of farmers and provide an understanding of the procedures for maintenance of infrastructure that already exists on agricultural land. The purpose of this study is to analyze the level of participation and to identify the factors that influence community participation in the management of swamp irrigation in the Anjir Serapat I area of ​​Kapuas Regency. This research method is a survey method that illustrates the effect of the variables incorporated in the existing irrigation network variables and the farmers' participation in maintaining tertiary irrigation networks. Based on the data collected for each variable, and after analysis with calculations, no relationship and significant effect were found together between the Technical Aspects (X1), Socio-Cultural Aspects (X2) and Socio-Economic Aspects (X3) towards participatory farmers (Y). With an average quantitative value of (22.37 <25), farmers are still classified as not being participatory in maintaining existing irrigation networks.